The impacts of the entrepreneurial conditions on economic growth: Evidence from OECD countries - Sofia Gomes; Jo\~ao J. M. Ferreira; Jo\~ao Morais Lopes; Luís M. Carmo Farinha (Economies, 2022)
This study aims to assess the impacts of entrepreneurial framework conditions on economic growth based on the level of economic development in transition-driven economies and innovation-driven economies. The data were organised into a panel (2000-2019) and obtained from the National Expert Survey (NES), the Global Monitor Entrepreneurship (GEM), and the World Bank. By applying the generalised method of moments (GMM) estimation, we found that R&D transfer has a negative impact on economic growth that is innovation-driven, but positively impacts transition-driven economies. The results further highlighted that regardless of the level of development of the country, business and professional infrastructure do not positively impact economic growth. However, taxes and bureaucracy and physical and service infrastructure were shown to positively impact only innovation-driven economies, as in transition-driven economies, they were shown to have negative impacts on economic growth. The present study contributes to a better understanding of the link between economic growth and the conditions for entrepreneurship in economies with different degrees of economic growth. This study can serve as a basis for policy makers to adjust or develop new policies to accelerate economic growth.
Keywords: 330; economic growth; entrepreneurship; framework conditions; Global Entrepreneurship Monitor (GEM); innovation-driven economies; transition economies; transition-driven economies